PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS KOPERASI UKM KOTA MAKASSAR - Sri Wahyuni; Samsul Rizal; Nurinaya (STKIP Subang, 2026)
This study aims to analyze the effect of work environment and organizational culture on employee performance at the Department of Cooperatives and SMEs, Makassar City. A quantitative approach was employed with a total population and sample of 78 employees through total sampling. Data were collected via a Likert scale questionnaire (1–5) and analyzed using multiple linear regression with SPSS. The results show that work environment has a positive and significant effect on employee performance (β=0.377; t=5.027; sig.=0.000), thus H1 is accepted. Organizational culture also has a positive and significant effect on employee performance (β=0.344; t=5.329; sig.=0.000), thus H2 is accepted. Simultaneously, both variables significantly affect employee performance (F=24.822; sig.=0.000). The coefficient of determination (R²=0.398) indicates that 39.8% of the variation in employee performance is explained by both variables, while the remaining 60.2% is attributed to other factors outside this model.